The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adsu.202100299
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Valorization of Lignin: A Key Focus on Pretreatment, Characterization, and Catalytic Depolymerization Strategies for Future Biorefineries

Abstract: In this regard, lignocellulosic biomass (LCB) is an attractive alternative due to its abundant availability, carbon neutral nature, and its ability to produce a wide range of fuels and chemicals. [11,12] LCB mainly consists of cellulose (30% to 50%), hemicellulose (20% to 35%), and lignin (15% to 30%), interlinked with each other via a complex bonding network. [13,14] Currently, most of the biorefineries are focusing on the utilization of carbohydrates (cellulose and hemicellulose) for producing bio-ethanol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 206 publications
(375 reference statements)
0
9
0
Order By: Relevance
“…Catalytic conversion of lignocellulosic biomass into platform chemicals and fuels has been intensified as a significant research topic over the past decade. 1,2 Upgradation of biomass as a renewable feedstock through a green and cost-effective route by minimizing waste generation is a challenging problem. It requires sustainable development of energyefficient materials, catalysts, and processes, following microwave (MW) and ultrasound technologies (UT), avoiding the use of volatile organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic conversion of lignocellulosic biomass into platform chemicals and fuels has been intensified as a significant research topic over the past decade. 1,2 Upgradation of biomass as a renewable feedstock through a green and cost-effective route by minimizing waste generation is a challenging problem. It requires sustainable development of energyefficient materials, catalysts, and processes, following microwave (MW) and ultrasound technologies (UT), avoiding the use of volatile organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Protonic ionic liquids that are produced via an acid-base neutralization process are relatively cost competitive and demonstrate high lignin-extraction efficiency [69]. The solubility of different types of lignin in various ionic liquids has recently been reviewed, and it was shown that ionic liquids possessing aromatic cations have high lignin solubility, while those with nonaromatic cations have lower solubility [70]. However, the lignin dissolution mechanism is not fully understood, and further evaluation is needed to understand the properties and potential of the extracted lignin [71].…”
Section: Next-generation "Greener" Ligninsmentioning
confidence: 99%
“…The lignin extraction yield of various deep eutectic solvents for various lignocellulosic feedstocks and pretreatment conditions have also been reviewed. Compared to other deep eutectic solvents ChCl/oxalic acid and ChCl/ lactic acid-based solvents had the best delignification yields [70]. In a recent study, these solvents were evaluated for lignin separation from rice straw.…”
Section: Next-generation "Greener" Ligninsmentioning
confidence: 99%
“…As destruction mechanism, a β‐O‐4 cleavage in the phenolic structures was assumed with hydrolytic cleavage of alkyl−phenyl bonds in phenolic structural units which are oxidized by HPA‐5 with subsequent acidolytic splitting of the β‐O‐4 linkages. Another discussed mechanism is the cleavage of alkyl‐phenyl bonds via one‐electron oxidation of the aromatic ring with subsequent hydrolysis [93,96] …”
Section: Catalytic Applications Using Bio‐based Feedstockmentioning
confidence: 99%
“…Another discussed mechanism is the cleavage of alkyl-phenyl bonds via one-electron oxidation of the aromatic ring with subsequent hydrolysis. [93,96] In a second study by Evtuguin et al [97] the authors used vanillyl and veratryl alcohol as monomeric model substrates for lignin. The results indicated that the first step of lignin oxidation is a one-electron oxidation of the substrate by HPA-5.…”
Section: Delignificationmentioning
confidence: 99%